REAL-TIME PLATOONING OF MOBILE ROBOTS: STUDY OF TRAJECTORY WITH OBSTACLE AVOIDANCE - BONG, DAVID CHUNG HUA (Universiti Teknologi PETRONAS, 2017)
Robot platooning is a robot positioning method, whereby a few robots will be moving in formation. Platooning has been a very commonly discussed technique especially for its applications on vehicles. However, up until now, it still has many issues that are preventing it from being implemented in real life and one of them is its irregular trajectory in the maintaining phase. In this project, study will be made on the real-time platooning trajectory in its maintaining phase under the most two common factors in real life, which are changes in velocity and presence of obstacle. By studying its performance under the mentioned factors, this project aims to contribute by having algorithm that can improve the platooning trajectory during its maintaining phase.In order to do so, two robotic cars are used as models to simulate real vehicles.